Investigating The Relationship Between Organizational Learning And Flexibility Of Employees In Education Department Of Sarpool-E-Zahab City - Ghanbari, Iran; Abdi, Nariman (The Turkish Online Journal of Design Art and Communication, 2016)
The flexibility of human resources is one of the most important aspects of organizational flexibility and is focused on adaptability of employee’s characteristics (such as knowledge, skills and behavior) with changing environmental conditions. This study aimed to investigating the relationship between organizational learning and flexibility of employees in education department of Sarpool-e-zahabcity. The study population included all employees of education in Sarpool-e-zahabcity which were 1,300 people. Among these samples using simple random sampling method, a sample of 297 subjects was selected according to Cochran formula. This study in terms of aim is applied research and in terms of data collection is descriptive and correlational. In this study, a questionnaire to collect data and to confirm the questionnaire validity from expert’s perspective and SPSS software was used to assess the reliability and Cronbach's alpha for organizational learning questionnaire and organizational learning both were above 0.7, indicating high reliability of the questionnaire. In this study, for data analysis, SPSS software and Pearson correlation and multiple regression were used, the results suggest that there is a significant positive relationship between organizational learning aspects (shared vision, organizational culture, team work and learning, knowledge sharing, system thinking, participative leadership and competence development) and employee’s flexibility, regression results indicate that the shared vision more than other variables affect the flexibility of employees.
Keywords: Organizational learning; Employee’s flexibility; Education department in Sarpool-ezahabcity